Measuring the Impact of Tourism Revenue on Economic Growth in Algeria during the Period 2005-2023 Using the ECM Error Correction Model - Bessouyach, Mouna; Mimouni, Yassine (Pomiar wpływu przychodów z turystyki na wzrost gospodarczy w Algierii w latach 2005-2023 z wykorzystaniem modelu korekcji błędów ECM, 2025)
This study aimed to measure the impact of tourism revenue on Algeria's economic growth during the period 2005-2023. Methodology: The author used the enterprise content management error correction model, with the aim of testing the long-term causal link between tourism revenue and economic growth, and testing joint integration. Results: After testing the stability of time chains, the study variables were found to be first-class reliable. The results of the estimates showed a causal link between the two variables in the short term. After testing the significance of the parameters, CointEq error correction coefficient was found to be negative and ethical. This explains the long-term balance between the positive impact study variables for both GDP and the change in tourism revenue. Implications and recommendations: It was possible to propose the following recommendations: promoting the community's tourism culture, developing the tourism infrastructure, and engaging with the private sector and launching tourism projects. Originality/value: This issue is of great importance due to the increased interest in the tourism sector in financing the economy, considered to be an alternative to petroleum wealth.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 4, s. 13-29
Keywords: tourism; tourism revenue; economic growth; causal relationship; error correction model; turystyka; przychody z turystyki; wzrost gospodarczy; związek przyczynowo-skutkowy; model korekcji błędów